2002
DOI: 10.1177/108471380200600402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compression on Speech Acoustics, Intelligibility, and Sound Quality

Abstract: time, use of compression hearing aids has increased dramatically, from half of hearing aids dispensed only 5 years ago to four out of five hearing aids dispensed today (Strom, 2002b). Most of today's digital and digitally programmable hearing aids are compression devices (Strom, 2002a). It is probable that within a few years, very few patients will be fit with linear hearing aids. Furthermore, compression has increased in complexity, with greater numbers of parameters under the clinician's control. Ideally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 166 publications
4
125
1
1
Order By: Relevance
“…Fewer than half (10 out of 26) of the subjects indicated that the highest intelligibility condition was also the one that gave the best quality. This finding is similar to results for amplification in hearing aids, where the response that gives the highest intelligibility is not necessarily the response that yields the highest listener preference (Punch and Beck, 1980;Souza, 2002).…”
Section: B Clinical Implicationssupporting
confidence: 82%
“…Fewer than half (10 out of 26) of the subjects indicated that the highest intelligibility condition was also the one that gave the best quality. This finding is similar to results for amplification in hearing aids, where the response that gives the highest intelligibility is not necessarily the response that yields the highest listener preference (Punch and Beck, 1980;Souza, 2002).…”
Section: B Clinical Implicationssupporting
confidence: 82%
“…Fast-acting AGC systems usually have lower compression ratios than AVC systems. High compression ratios (above about 3) are avoided, as these have been shown to have deleterious effects on speech intelligibility [35,36].…”
Section: Compensation For Threshold Elevation and Loudness Recruitmentmentioning
confidence: 99%
“…There is a rich literature on the impact of compression on speech intelligibility, with reviews provided by Dillon (1996) and Souza (2002), among others. Despite much research, there remains a lack of consensus on how compression should be implemented in hearing devices.…”
Section: Introductionmentioning
confidence: 99%